Changes in Gingival Crevicular Fluid Volume and Flow Rate During Orthodontic Treatment - Najwa A., Nassrawin (Journal of Dentistry And Oral Implants, 2016)
Background: Gingival crevicular fluid (GCF) is regarded as a promising medium for detection of periodontal disease activity. bone loss is a major feature of periodontal disease, although we are unable to determine the time of this bone loss and therefore periodontal disease activity. During orthodontic treatment small forces are applied, resulting in bone remodeling which allows tooth movement. Orthodontic model may be used as a preliminary stage in evaluating gingival crevicular fluid role in bone turnover. Aims: To detect GCF and to monitor it's volume and flow rate following orthodontic activation, and to determine at what stage inflammation and bone resorption reach their maximum. Materials and Methods: GCF samples were collected from 10 adult orthodontic patients (mean age = 22.3 , range 20-24year) on 3,7,10,14,21,28,35 days after activation of orthodontic appliance, from the tooth surface where bone resorption was expected to occur. A total of 330 GCF sample were collected using filter paper strip, the volume measured by weighing. Results: An insignificant increase in GCF volume and flow rate was noted in the tenth day after activation of the orthodontic appliance activation. At 35 days GCF reached its minimum flow rate. There was considerable variation between subjects and between the same subject on different days Conclusion: Increase in GCF volume and flow rate reflects the effect of orthodontic adjustment rather than oral hygiene, as there were no clinical inflammatory changes during the period of orthodontic treatment studied.
Keywords: Gingival crevicular fluid volume; flow rate; orthodontic treatment.